PENGARUH METODE PERKAWINAN TERHADAP KEBERHASILAN KEBUNTINGAN DOMBA LOKAL PALU - Rudiah Rudiah (Universitas Tadulako, 2008)
The study was conducted at the eksperimental station Kawatuna Sub District, Palu City, Central Sulawesi Province from January 2002 until Mei 2002. Thirty four of non pregnant Palu Local sheep were used. The sheep were devided in two groups; the first group consisted of 17 ewes were prepared for natural mating, whereas the second group for artificial mating. Both groups were estrus induced using intramuscularly injection of 1,25 cc PGF2µ (reprodin) per ewe. Two days after application of PGF2µ when the animal showed estrus, the natural mating and artificial insemination were conducted. The research results showed that the mating method significantly affected (P<0,05) on successful pregnancy. The artificial insemination method produced hingher number of pregnancy than the natural mating. The conception rate of the Palu Local sheep that mating by artificial insemination were 12 sheep (80 %) compared to only 6 sheep (40 %) by natural method